Phytoremediation of Heavy Metals Spiked Soil by Polyscias fruticose - Naseer Inuwa, Durumin Iya; Zaini, Assim; Isa, Ipor; Saminu Murtala, Yakasai; Binta Hadi, Jume; Shina, Ismail Sadiq (Oriental Scientific Publishing Company, 2019)
This study was to assess the phytoremediation potential of Polyscias fruticose in the removal of heavy metals from spiked soil. P. fruticose cuttings were transplanted then grown on 2.00 kg soil spiked with several heavy metals in polyethylene bags. The experiment was conducted for 300 days and concentrations of heavy metals in plant and soil over the growth period were determined. Appreciable concentrations of heavy metals in P. fruticose parts were obtained. The indices used to show the ease of heavy metals uptake and translocation indicated that Co, Cr, Mn, Ni and Pb displayed the greatest ease of absorption while Zn, Fe and Cu were accumulated in the root but not translocated to the shoot. The results obtained shows that this study pioneered the use of P. fruticose in the phytoremediation of several heavy metals spiked soil at a greenhouse level.